2020
DOI: 10.3390/genes11111272
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Diversity in Sporadic Breast Cancer in a Latin American Population

Abstract: Among Latin American women, breast cancer incidences vary across populations. Uruguay and Argentina have the highest rates in South America, which are mainly attributed to strong, genetic European contributions. Most genetic variants associated with breast cancer were described in European populations. However, the vast majority of genetic contributors to breast cancer risk remain unknown. Here, we report the results of a candidate gene association study of sporadic breast cancer in 176 cases and 183 controls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Inclusion criteria: (1) all included studies are observational studies. (2) The main exposure of study was smoking including active and passive smoking, and the outcome was BC risk. (3) All studies included available data which reported the relationship between smoking and BC.…”
Section: Selection Criteriamentioning
confidence: 99%
See 2 more Smart Citations
“…Inclusion criteria: (1) all included studies are observational studies. (2) The main exposure of study was smoking including active and passive smoking, and the outcome was BC risk. (3) All studies included available data which reported the relationship between smoking and BC.…”
Section: Selection Criteriamentioning
confidence: 99%
“…Exclusion criteria: (1) the study was conducted on BC population and used mortality or recovery rate as the outcome. (2) The study was published in duplicate. (3) The study was not published in English.…”
Section: Selection Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the present study suggested that this VUS is probably benign. Supporting this, recent meta-analyzes described this VUS to be a low-risk variant for breast cancer, demonstrating its possible protective behavior ( 51 , 52 ).…”
Section: Discussionmentioning
confidence: 64%
“…Thus, exploring genetic diversity in underrepresented populations is crucial for a comprehensive understanding of health and disease in diverse human populations. To this end, our group has made efforts in integrated genomics and epigenetics studies on complex diseases such as cancer and preterm birth, aiming to identify biomarkers in Latin American populations (Brignoni et al 2020;Cappetta et al 2015Cappetta et al , 2021Pereyra et al 2016Pereyra et al , 2019.…”
Section: Introductionmentioning
confidence: 99%